No way to die - Easley, Warren C (Easley, Warren C. Cal Claxton Oregon mysteries., 2019)
Attorney Cal Claxton, now well-established in his Oregon law practice after breaking off his career as a high-powered LA prosecutor, just wants to go fishing with his daughter, Claire, and he knows the best place<U+2015>the coastal area south of Coos Bay. But their vacation takes a dark turn with the discovery of a body in the river. As an investigation is launched into the suspicious death, Cal and Claire find themselves drawn into the life of the local bookshop owner and vocal environmental activist, whose grandson was convicted for murder at age sixteen. She believes he was wrongly accused and convinces Cal to reexamine the case. Together, Cal and Claire dig deep into the secrets and crumbling alliances that form the foundation of this small coastal community, and what they find could spell doom for them both...